The EU's new borderland : cross-border relations and regional development /: cross-border relations and regional development. (2016) - Jakubowski, Andrzej, 1980-; Miszczuk, Andrzej; Kawałko, Bogdan; Komornicki, Tomasz, 1963-; Szul, Roman
No abstract available